Faktor-Faktor yang Mempengaruhi Niat Penggunaan Sistem Informasi Terkomputerisasi pada UKM (Pendekatan Theory of Planned Behavior) - Kurnia Rizki Amanda; MI Mitha Dwi Restuti (Universitas Kristen Maranatha, 2017)
Abstract The information system is a set of related components which serves to collect, process store, and distribute information either done manually or with the aid of a computer to generate information that is useful in decision making. This study aims to examine the factors that affect interest in the use of computerized information systems by perpetrators of Small and Medium Enterprises (SMEs) for decision making by using three variables of the Theory of Planned Behaviour proposed by Ajzen (1991) which are attitude, subjective norms, and perceived behavior control. Fifty-two SMEs in Salatiga have been surveyed and used as a sample. Results from multiple regression analysis showed that perceived behavior control variables affect the interest of the use of computerized information systems. The results showed that the SMEs believe that the use of computerized information systems is easy to do so that SMEs are interested in using the computerized information systems.While the attitude and subjective norm does not affect the interest in the use of computerized information systems, which means that the SMEs have the notion that using computerized SI is not important and the perception of the people around did not affect the interest of SMEs to use the computerized information system. Keywords: Interest in the use of computerized information systems; Small and Medium Enterprises (SME); Theory of Planned Behaviour